Archaeological Micromorphology Self‐Evaluation Exercise. Issue 1 (26th November 2015) - Shahack‐Gross, Ruth
Abstract : An intercommunity exercise was carried out between July 2011 and May 2013 among practitioners of archaeological micromorphology. The exercise was designed to quantitatively evaluate the accuracy of basic material identification using petrography only. Over 30 people participated. Participants were asked to provide general as well as detailed (mineralogical) identifications. Results were calculated in percentages of correct answers/identifications. The highest personal scores were in the order of 70% correct answers. This general low score primarily reflects misunderstanding related to filling out the test form. The test results therefore allow deciphering of only coarse trends. A learning curve is identified among students (0–4 years of experience), while among post‐PhD researchers there appears to be a learning "saturation." Identification scores were better for archaeological materials than for geogenic materials (i.e., rocks). Mineralogy is generally poorly known. Materials that appear to require more basic research in order to develop clear petrographic guidelines for identification include calcined bone, wood ash versus lime plaster, and opaque materials (except for wood charcoal). Students of micromorphology are encouraged to devote time to studying core geology courses in order to obtain basic knowledge of rocks and minerals. The overall implications of this test resonate on geoarchaeology in general.